EFEKTIVITAS MEDIA ARTIFICIAL INTELLIGENCE GOOGLE GEMINI DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPALANASI SISWA KELAS VIII SMPN 3 SODONG HILIR KABUPATEN TASIKMALAYA - Agustriani, Dina; Nurwahidah, Lina Siti; Budi, Asep Setia; Nurjanah, Nina Siti (IdeBahasa, 2025)
The ability to write explanatory texts is a crucial component of Indonesian language learning at the junior high school level. One of the common challenges is students’ low performance in organizing ideas and structuring texts coherently. This study aims to examine the effectiveness of the Artificial Intelligence-based media Google Gemini in improving students’ ability to write explanatory texts. The research employed a quantitative method with a quasi-experimental design using a one-group pretest-posttest model. The sample consisted of one class, namely class VIII-A of SMPN 3 Sodonghilir, with a total of 32 students. Research instruments included a writing test and a student motivation questionnaire. Data were collected through written tests and analyzed using the Wilcoxon Signed Ranks Test and simple regression analysis. The results showed a significant improvement in scores from a pretest average of 28.97 to a posttest average of 87.97, with a significance value of 0.000. Regression analysis indicated that learning motivation did not significantly influence learning outcomes, with a significance value of 0.492. Google Gemini proved to be an effective tool for enhancing students’ ability to write explanatory texts.